2022
DOI: 10.4041/kjod21.267
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pharyngeal airway in Korean adolescents according to skeletal pattern, sex, and cervical vertebral maturation: A cross-sectional CBCT study

Abstract: Objective: To investigate airway volumes using cone-beam computed tomography (CBCT) by skeletal patterns, sex, and cervical vertebral maturation (CVM) stages in Korean adolescents. Methods: The sample consisted of pretreatment CBCT and cephalograms of 95 adolescents (aged 12-19) obtained out of 1,611 patients examined for orthodontic treatment from 2018 to 2020 in Kyungpook National University Dental Hospital. The samples were classified into two sex groups; three skeletal pattern groups, four chronological ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…More specifically, a tendency for an inverse relationship between lower pharynx (velopharynx and oropharynx) volume and ANB angle was reported [ 11 ], with the oropharyngeal volume being reduced in those with mandibular retrusion and increased in those with mandibular protrusion [ 12 ]. Similarly, smaller SNB values were associated with smaller nasopharyngeal and oropharyngeal volumes, with differences between male and female patients becoming more evident at the completion of growth, while the vertical skeletal configuration did not seem to influence the upper airway volumes [ 13 ]. Contrary to this, another study found that facial divergence was associated with differences mainly in the oropharyngeal volumes, with hypodivergent patients having greater volumes than hyperdivergent ones [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, a tendency for an inverse relationship between lower pharynx (velopharynx and oropharynx) volume and ANB angle was reported [ 11 ], with the oropharyngeal volume being reduced in those with mandibular retrusion and increased in those with mandibular protrusion [ 12 ]. Similarly, smaller SNB values were associated with smaller nasopharyngeal and oropharyngeal volumes, with differences between male and female patients becoming more evident at the completion of growth, while the vertical skeletal configuration did not seem to influence the upper airway volumes [ 13 ]. Contrary to this, another study found that facial divergence was associated with differences mainly in the oropharyngeal volumes, with hypodivergent patients having greater volumes than hyperdivergent ones [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…CBCT, and reported conflicting results. Elagib et al[16] found that skeletal patterns affect airway volume. However, the authors reported that age and sex also significantly influence airway variables.…”
mentioning
confidence: 99%